Debunking Myths and Misinformation in Cervical Cancer: A Narrative Review on Navigating Complex Treatment Choices in Locally Advanced Cases and Exploring Beyond Standard Protocols - Mustafa Zelal Muallem; Ahmad Sayasneh (Diagnostics)
Cervical cancer remains a significant health challenge globally, with locally advanced cervical cancer (LACC) representing a particularly complex subset due to its diverse definitions and varied treatment approaches. The absence of randomized controlled trials comparing the upfront radical surgery followed by concurrent chemoradiotherapy (CCRT) or chemotherapy alone for clearly defined risk factors for LACC hinders the development of standardized treatment protocols, leading to disparities in patient outcomes across different healthcare settings. This paper seeks to underline the necessity of a consensus on the definition of LACC and aims to comprehensively and critically review the existing literature trying to harmonize treatment strategies and improve prognostic outcomes. Our analysis suggests a multimodal approach for treating FIGO IB3, IIA2, and selected IIB cases at facilities capable of delivering highly curative nerve-sparing surgical interventions, with the goal of bridging the gap in current treatment methodologies. Preliminary findings suggest that adopting a standardized definition could facilitate more consistent treatment outcomes and enhance comparative research.